Pengawasan Keuangan, Kepatuhan Regulasi, dan Teknologi Informasi Akuntansi Terhadap Kinerja Aparatur Pemerintahan Desa Sekecamatan Tanon Sragen - Isnaini Taufik Hidayah; Yuwita Ariessa Pravasanti; Desy Nur Pratiwi (Nur Science Institute, 2026)
This study aims to examine the effect of financial supervision, regulatory compliance, and accounting information technology on the performance of village government officials in Tanon District. This research employs a quantitative approach using a survey method involving 80 respondents, including village heads, secretaries, and administrative staff in finance, planning, and governance. Data were analyzed using multiple linear regression. The results indicate that financial supervision, regulatory compliance, and accounting information technology have a positive and significant effect on the performance of village officials, both partially and simultaneously. The model explains 57.2% of the variance in officials’ performance, suggesting that these variables are key determinants in improving administrative performance at the village level. These findings highlight the importance of strengthening financial supervision systems, enhancing regulatory compliance, and optimizing the use of accounting information technology to support sustainable improvements in village government performance.